"The Holy Spirit as bond" in Calvin's thought: its functions in connection with the extra Calvinisticum - Lee, Daniel Y. K. (University of Edinburgh, 2010)
In the overall plan of our study we will attempt in chapter 2 to trace the theological intention behind the first text of the extra Calvinisticum and see how Calvin subsequently invoked the notion "the Holy Spirit as bond" to enhance his teaching. A short exposition of the functions of the notion in the eucharistic context will also be given as an outline of the following chapters. In chapters 3, 4 and 5, we will examine the relation between the Holy Spirit and the person and work of Christ. First, we will examine Calvin's understanding of Christ's and the Spirit's aseity, as well as his concept of person in the trinitarian context. This will help us to clarify the relation between the extra Calvinisticum and Filioque (chapter 3). Next, we will explore Calvin's concept of person in the christological context and its relation with the extra Calvinisticwn. We will see how Calvin transposed the conventional problem of two natures to a problem of offices of the Mediator (chapter 4). This will prepare us to discuss further how a corresponding offices-pneumatology was invoked to accomplish these offices of the Mediator in acquiring righteousness and life for us (chapter 5). In chapter 6, we will see how believers receive the salvific benefits accomplished in this redeeming work through the communio Christi vinculo Spiritus. We will trace how the notion communio Christi was invoked to safeguard the unity and differentiation of salvific benefits throughout the various editions of the Institutes and how it finally emerged with vinculum Spirit to form the crowning conception in Book Three of the definitive edition of the Institutes. Based on this, we will proceed to examine the works of the Holy Spirit in imparting the salvific benefits. In chapter 7, we will explore how the Holy Spirit unites believers in the present life to the Christ in the future coming. This will also bring us to the termination of the extra Calvinisticum in the eschaton.
Keywords: Religion